A survey on design optimization studies of induction motors during the last decade - (:unkn) unknown (My University, 2009)
0

Optimization methods are widely used in design of electromagnetic devices throughout the years. Moreover, there are many literature surveys on application of optimization methods to electromagnetic devices. This study is focused on optimization techniques in design optimization of induction motors to help researchers to gain background knowledge of most recent studies. In this paper, firstly, induction motor types and optimization methods are introduced. Secondly, brief explanations on each application of optimization methods are given in chronological order and according to induction motor types. Lastly, these studies are classified and evaluated.
Keywords: Mühendislik, Elektrik ve Elektronik